Assessing Phonological Processing in Children With Speech Sound Disorders. - Roepke, Elizabeth (Perspectives of the ASHA Special Interest Groups, 2024)
Purpose: Phonological processing skills, or using phoneme knowledge to process language, in preschool- and kindergarten-age children are an important indicator of children's future reading abilities. However, assessing phonological processing skills can be difficult in children with speech sound disorders because scoring often requires that children produce speech sound accurately. This tutorial presents assessment tasks that are appropriate for children with speech sound disorders to better identify children with phonological processing difficulties. Conclusions: The following phonological processing assessment tasks are recommended for children with speech sound disorders: receptive tasks for phonological awareness, the Syllable Repetition Task for phonological memory, and limited letter choices for rapid automatized naming in phonological retrieval tasks. These tasks can be modified for multilingual children. Appropriate assessment of phonological processing skills will help speech-language pathologists in differential diagnosis of children with true phonological processing difficulties and children whose speech sound errors may mask phonological processing abilities. Assessment of phonological processing skills is particularly important for children with speech sound disorders, whose speech errors may be evidence of phonological processing difficulties.